Die moeder-kind verbintenis - E.M. Maclure (Curationis, 1979)
In antenatal clinics, maternity homes and doctors’ practices, more can be done to promote understanding of the patient’s needs and of the lack of mother-child bonding factors. The importance of early experiences which create a bond between mother and baby cannot be sufficiently stressed. The sooner the mother is allowed to handle, inspect and suckle her baby, the less complicated will be the most important first impression and the easier the development of mutual care.